The Influence Of Work Discipline And Work Environment On Employee Performance Lpi Foundation Al- Muttaqin Tasikmalaya City - Raisha Ameliza Az’zahra; Dian Indiyati (International Journal of Economics, Business and Innovation Research, 2024)
Education has an important role in state development and economic growth, with significant changes in the world of education according to the times. This transformation contributes greatly to the progress of society, including in the field of HR management in educational institutions such as the Al-Muttaqin Foundation Islamic Development Institute (LPI). Efficient human resources and employee performance are critical to the success of public organizations. This study examines work discipline, work environment, and employee performance at LPI Al-Muttaqin Foundation as well as the effect of work discipline and work environment on employee performance. Using a quantitative approach with questionnaires distributed to 110 employees at LPI Al-Muttaqin Foundation Tasikmalaya City through the saturated sample method, the data were analyzed using descriptive and path analysis with IBM SPSS version 25. The results show that work discipline is in the "discipline" category, while the work environment and employee performance are in the "good" category. Work discipline and work environment have a significant influence on employee performance both partially and simultaneously. The total effect of work discipline and work environment on employee performance is 78.9%, with 21.1% influenced by other factors.